Analisis Tanda Dalam Karya Seni Grafis Reza Sastra Wijaya Kajian Semiotika Peirce - Mukhsin Patriansah; Reza Sastra Wijaya (JURNAL RUPA, 2021)
The form of art is a representation of a reality. In representing this reality, an artist tries to restructure signs or even create new signs. The expression poured into the medium of art is a novelty and has never been formulated at all through existing codes, thus creating a new discourse. With all his abilities, the artist creates new signs in his work by associating an object with another object based on generally accepted rules (conventions). In this study, the author uses Peirce's semiotic theory to analyze the sign system in Reza Sastra Wijaya's graphic art. Contextually, the correlation of the sign system contained in this work with the title of the work, namely "the fraudulent method" and the subject matter or main idea of ??the case of "bribery" can be interpreted that with "bribes or kickbacks" everything can be achieved and achieved without following the rules. -Rules that apply by convention. This symbolic message is what the artists want to convey through this graphic art work which is associated with the game of chess, which is a game of fighting tactics and strategies in achieving a victory. This study aims to provide knowledge to academicians about the study of semiotics, so that they can find out how the sign system is presented in art and design works.